Maintaining the yield of edible rice in a warming world - Fitzgerald, Melissa A.; Resurreccion, Adoracion P. (Commonwealth Scientific and Industrial Research Organisation, 2009)
High temperature increases the amount of chalk in rice (Oryza sativa L.) grains, which causes grains to break during polishing, lowering the amount of rice for consumption. Here, we examined the effect of elevated temperature on substrate supply to the panicle, the capacity of the panicle to produce edible grains, and underlying factors affecting yield of edible grain in two varieties. During grain-filling, substrate supply followed a bell shaped curve, and high temperature significantly shortened supply time. The rate of grain-filling did not change and paddy yield fell in both varieties. In high temperature, yield loss in IR8 was due to lighter grains relative to those grown in cool temperature, but in IR60, it was due to the early sacrifice of 30% of the spikelets. The yield of edible rice was zero for IR8 and ~60% for IR60 for the high temperature treatments, and 100% for IR60 and 70% for IR8 in the cool temperature. IR60 differs from IR8 in regulation of substrate supply, architecture of the panicles and the capacity of the panicles to alter sink size in response to the stress and these factors may be responsible for the difference in edible rice in the two varieties.